Non-linear association of sleep duration with osteoarthritis among U.S. middle-aged and older adults - Guoliang Ma; Bo Xu; Zhizhuang Wang; Weili Duan; Xin Chen; Liguo Zhu; Bowen Yang; Dian Zhang; Xiaokuan Qin; He Yin; Xu Wei (BMC Public Health)
Abstract Background The duration of sleep is linked to a range of disorders. Osteoarthritis (OA) stands as one of the most prevalent forms of arthritis and serves as a leading cause of disability. The correlation between the duration of sleep and OA remains ambiguous. Research indicates that waist circumference correlates with sleep duration and OA, respectively. This study aimed to investigate the association of sleep duration with OA and the mediated effect of waist circumference. Methods The study sample comprised adults who were participants in the National Health and Nutrition Examination Survey (NHANES) between 2011 and 2018. Insufficient sleep is characterized by a duration of less than seven hours, whereas 7–8 h is considered appropriate, and 9 h or more is categorized as a long sleep duration. Three models were employed in this study. Model 1 was not adjusted for any covariates, while Model 2 was adjusted for sex, age, and race. Model 3 has been adjusted to account for all covariates. Utilizing multivariable logistic regression, subgroup analysis, interaction tests and smoothing curve fitting, the correlation between sleep duration and OA was explored. The mediating effect of waist circumference on the association between sleep duration and OA was investigated through mediation analysis. Results In this study, 9380 did not have OA, while 2424 were diagnosed with the ailment. After multivariable adjustment, the odds ratios (OR) for OA were 1.19 (95% CI 1.06, 1.34; P = 0.0026) for people with insufficient sleep duration and 1.18 (95% CI 1.03, 1.35 P = 0.0142) for participants with long sleep duration. Sleep duration and the incidence of OA were found to be related in a U-shaped manner. Additionally, 12.1% of the correlation between sleep duration and OA appeared to be mediated by waist circumference. Conclusions Increased OA was found to be correlated in a U-shaped manner with sleep duration in the middle-aged and elderly cohorts. Both insufficient and long sleep duration contribute to an elevated risk of developing OA. A potential mediating factor in the association between OA and sleep duration is waist circumference. Focus on sleep health and visceral obesity in middle-aged and older adults is necessary.